Characterization of NiCrAlY Layers Deposited on 310H Alloy Using the EB-PVD Method After Oxidation in Water at High Temperature and Pressure - Florentina Golgovici; Aurelia-Elena Tudose; Laurențiu Florin Mosinoiu; Ioana Demetrescu (Applied Sciences, 2025)
In this paper, the oxidation behavior of the 310H alloy coated with NiCrAlY using the EB-PVD method is studied after exposure to water at a high temperature and pressure (550 °C and 25 MPa) for different periods (720 h, 1440 h, and 2160 h). The Electron Beam Physical Vapor Deposition (EB-PVD) method was used to obtain the NiCrAlY coating. After testing, the coating performance was carried out by gravimetric analysis, grazing incidence X-ray diffraction (GIXRD), scanning electron microscopy (SEM), electrochemical impedance spectroscopy (EIS), and the linear polarization method. GIXRD analysis highlighted the presence of chromium oxide (Cr2O3) and the Corundum phase (Al2O3) on the surface of the oxidized NiCrAlY-coated 310H samples. On the surface of the 310H alloy, the existence of the NiCrAlY coating and of the oxide film generated during oxidation are evident according to the EIS spectra, which show two capacitive semicircles in the Nyquist diagram. Furthermore, an increase in diameter semicircles with the oxidation time increasing was observed in the Nyquist diagram. Very low corrosion rates of 4.8 × 10−5 mm × year−1, which were observed for oxidization for 2160 h NiCrAlY-coated samples, indicated that the oxide films are more protective and provide better corrosion resistance, which is also evidenced by the EIS analysis. Considering the obtained results, a significant relationship between the electrochemical technique, scanning electron microscopy, and gravimetric analysis was established.